Social discourse on cyberbullying in the digital press: An analysis for social intervention professionals - Millán-Franco, Mario; Domínguez de la Rosa, Laura (Revista Prisma Social, 2023)
Given the influence of the mass media on constructing realities and opinions, we investigated how the phenomenon of cyberbullying is presented in the digital versions of the high-profile newspapers El País and El Mundo. A qualitative method was used. In the first stage, thematic analysis was applied to the textual content of the selected news items. Three themes were obtained:1: Metamorphosis of school bullying: the emergence of cyberbullying; 2: Patriarchy in cyberbullying: gender issues; and 3: The COVID-19 pandemic: a breeding ground for cyberbullying. In the second stage, discursive analysis was conducted to study in further depth the interconnected contents found in the three themes. The following IR was obtained: An incipient prevention-intervention approach against cyberbullying. The results suggest that there is a pressing need to plan and implement systematic and well-coordinated measures. To do so, special emphasis must be placed on sensitizing society in general and social intervention professionals in particular to these new ways of exercising violence such that they support and contribute socially to this initiative. As part of their political agendas, all the institutions involved should prioritize the struggle against the current scourge of cyberbullying.